The BrainScaleS-2 Accelerated Neuromorphic System With Hybrid Plasticity - Pehle, Christian; Billaudelle, Sebastian; Cramer, Benjamin; Kaiser, Jakob; Schreiber, Korbinian; Stradmann, Yannik; Weis, Johannes; Leibfried, Aron; Müller, Eric; Schemmel, Johannes (Frontiers in Neuroscience, 2022)
Since the beginning of information processing by electronic components, the nervous system has served as a metaphor for the organization of computational primitives. Brain-inspired computing today encompasses a class of approaches ranging from using novel nano-devices for computation to research into large-scale neuromorphic architectures, such as TrueNorth, SpiNNaker, BrainScaleS, Tianjic, and Loihi. While implementation details differ, spiking neural networks -- sometimes referred to as the third generation of neural networks -- are the common abstraction used to model computation with such systems. Here we describe the second generation of the BrainScaleS neuromorphic architecture, emphasizing applications enabled by this architecture. It combines a custom analog accelerator core supporting the accelerated physical emulation of bio-inspired spiking neural network primitives with a tightly coupled digital processor and a digital event-routing network.